(untitled) (Research, Society and Development, 2022)
Objective: To apprehend the representations of health professionals regarding musical intervention for newborns eligible for palliative care. Method: This is a qualitative study, based on the Theory of Social Representations. The study setting was the Neonatal Intensive Care Unit of a university hospital in southern Brazil. The collection took place from January to March 2022, health professionals working in the Neonatal Intensive Care Unit participated in this study. Data were analyzed using the methodological framework of the Collective Subject Discourse. Results: 15 health professionals participated in this study, including: nursing technicians, nurses, doctors and physiotherapists From the analysis of the speeches, 4 central ideas (CI) emerged: CI1- Music therapy and palliative care; CI2- Music therapy as a strategy for palliative care; IC3- Benefits of music therapy; IC4- Harms of music therapy. Final Considerations: It is essential to understand that there are many difficulties in inserting the eligibility of palliative care and in implementing music therapy. Even in this scenario, health professionals demonstrated to visualize the benefits of music therapy and the need for the presence of a qualified professional for its application. In addition, the study identified the interest of professionals in the use of the practice in newborns eligible for palliative care, recognizing the importance of this care strategy.